2012
DOI: 10.1371/journal.pone.0041978
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Detection of Plesiomonas shigelloides by Loop-Mediated Isothermal Amplification of the hugA Gene

Abstract: Plesiomonas shigelloides is one of the causative agents of human gastroenteritis, with increasing number of reports describing such infections in recent years. In this study, the hugA gene was chosen as the target to design loop-mediated isothermal amplification (LAMP) assays for the rapid, specific, and sensitive detection of P. shigelloides. The performance of the assay with reference plasmids and spiked human stools as samples was evaluated and compared with those of quantitative PCR (qPCR). No false-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This value is similar to those reported in previous studies, which detected 1, 20, 7.9, and 3.8 CFU per reaction for Escherichia coli O157:H7, Plesiomonas shigelloides, C. jejuni, and C. coli, respectively (30,31,40). The sensitivity of the LAMP method developed in this study was 10-to 1,000-fold higher than that of conventional PCR or multiplex PCR (30,40). In concordance with the results of previous studies, LAMP showed 100-fold-greater sensitivity than conventional PCR or multiplex PCR.…”
Section: Discussionsupporting
confidence: 92%
“…This value is similar to those reported in previous studies, which detected 1, 20, 7.9, and 3.8 CFU per reaction for Escherichia coli O157:H7, Plesiomonas shigelloides, C. jejuni, and C. coli, respectively (30,31,40). The sensitivity of the LAMP method developed in this study was 10-to 1,000-fold higher than that of conventional PCR or multiplex PCR (30,40). In concordance with the results of previous studies, LAMP showed 100-fold-greater sensitivity than conventional PCR or multiplex PCR.…”
Section: Discussionsupporting
confidence: 92%
“…A range of PCR assays targeting different genomic fragments have been developed for the detection of P. shigelloides (Table 9) (42,51,221,222,223,224,225). One of the earliest assays was configured by González-Rey et al (42) and targeted a specific variable region of the 23S rRNA gene previously identified by Van Camp et al (226).…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
“…Primers targeting the hugA gene were shown to have high specificity for P. shigelloides when tested with a range of Gramnegative strains of different genera and were used by these workers to detect the organism in saltwater fish. Meng et al (225) developed a detection assay for P. shigelloides targeting hugA ( Table 9) that is based on a loop-mediated isothermal amplification (LAMP) reaction mediated by Bst DNA polymerase (227). When used to test spiked human stool samples, the assay proved to be more accurate, sensitive, and faster (in assay time) than quantitative PCR.…”
Section: Laboratory Identification Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of 6 oligonucleotides promotes the speed of the amplification and the specificity, and the output can be up to 10 9 copies of target DNA molecules within 1 h. The products of LAMP can be visualized in different ways, such as turbidity caused by the precipitation of magnesium pyrophosphate, gel electrophoresis, and the addition of complex ometric dyes, such as SYBR green to observe fluorescence under UV light. Recent reports showed that LAMP had been widely used in the detection of viruses and bacteria (16)(17)(18), but it has only recently been applied to some species in the filamentous fungi and yeast genera, including Aspergillus flavus, Aspergillus parasiticus, Aspergillus nomius, and Histoplasma capsulatum but not A. fumigatus as yet (19,20).…”
mentioning
confidence: 99%